Editorial (2018)
Legal research, which has evidenced different scenarios, is currently necessary for the study and application of law; and it is in this sense that it is appropriate to affirm that legal research in the Colombian State has denoted changes of relevance that allow corroborating the transformation of the law. This is due to the tendency of legal research to analyze complex realities that the contemporary Colombian society is experiencing. It is in this sense that academic production can be confirmed as a result of research projects, which analyze and contextualize legal institutions that in the past were untouchable, and that, to date, thanks to scientific research, have been tried to contextualize and explain within the framework of contemporary Colombian reality; or also, it has been possible to corroborate positive or negative criticisms of existing legal institutions and that up to now have not been able to be framed or harmonized in regards to the reality required by the legal field.From the aforementioned perspective, the IUSTA journal in its July-December 2018 edition presents its readers with topics that relate to the diligent analysis of novel legal institutions or that require a better contextualization in relation to the legal, social and political reality of the Colombian State.